Chronic kidney disease epidemiology collaboration-derived glomerular filtration rate performs better at detecting preclinical end-organ changes than alternative equations in black Africans. Issue 6 (June 2016) - Booysen, Hendrik L.; Woodiwiss, Angela J.; Raymond, Andrew; Sareli, Pinhas; Hsu, Hon-Chun; Dessein, Patrick H.; Norton, Gavin R.
Abstract : Supplemental Digital Content is available in the text Abstract : Aim: To identify whether the more recently developed equation for estimated glomerular filtration rate (eGFR) [Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI)] is more closely associated with end-organ changes than previous equations in a group of black African descent. Methods: In 1221 randomly recruited participants of black African ancestry in South Africa, we evaluated serum creatinine concentrations, echocardiographic left ventricular mass index ( n  = 833), carotid-femoral (aortic) pulse wave velocity (PWV) ( n  = 1053) and carotid intima–media thickness ( n  = 633). We calculated eGFR from the Jelliffe, five Cockcroft–Gault, Salazar–Corcoran, Modification of Diet in Renal Disease (MDRD) and CKD-EPI equations. Results: After multivariate adjustments, eGFR calculated from all formulae was inversely associated with left ventricular mass index ( P  < 0.0001) and PWV ( P  < 0.05 to <0.001), but not with carotid intima–media thickness ( P  > 0.08). However, although eGFR determined from all equations except Cockcroft–Gault lean body weight or adjusted body weight was independently associated with left ventricular hypertrophy ( n  = 390 of 833), CKD-EPI-derived eGFR, but not eGFR determined from alternative equations, was independently associated with an increased PWV ( n  = 88 of 1053). eGFR derived from the CKD-EPI and MDRD equations showed a better performance (area under the receiver operator characteristic curve) for the detection of left ventricular hypertrophy ( P  < 0.0005) than eGFR determined from alternative equations. Conclusions: In black Africans, eGFR derived from the CKD-EPI equation is better at detecting end-organ measures than eGFR derived from either the MDRD or alternative equations. To enhance risk prediction in black African communities, eGFR calculated from the CKD-EPI equation may be preferred to other equations.